2017
DOI: 10.1155/2017/7123919
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanotechnology of TiO2Improves Physical-Chemical and Biological Properties of Glass Ionomer Cement

Abstract: The aim of this study was to assess the performance of glass ionomer cement (GIC) added with TiO2 nanotubes. TiO2 nanotubes [3%, 5%, and 7% (w/w)] were incorporated into GIC's (Ketac Molar EasyMix™) powder component, whereas unblended powder was used as control. Physical-chemical-biological analysis included energy dispersive spectroscopy (EDS), surface roughness (SR), Knoop hardness (SH), fluoride-releasing analysis, cytotoxicity, cell morphology, and extracellular matrix (ECM) composition. Parametric or nonp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 35 publications
5
54
0
2
Order By: Relevance
“…Other studies, however, have confirmed the reinforcing effect of nanoparticles [80,82,83]. A variety of nanoparticles have been used, such as titanium dioxide nanotubes [83] and nanoparticles [81,82], alumina nanoparticles [83], and zirconia nanoparticles [84]. Glass-ionomer cements with added nanoparticles have been found to be easier to mix than those without nanoparticles [85] and to contain fewer air voids or internal micro-cracks [86].…”
Section: Nanoparticle Reinforcementmentioning
confidence: 99%
“…Other studies, however, have confirmed the reinforcing effect of nanoparticles [80,82,83]. A variety of nanoparticles have been used, such as titanium dioxide nanotubes [83] and nanoparticles [81,82], alumina nanoparticles [83], and zirconia nanoparticles [84]. Glass-ionomer cements with added nanoparticles have been found to be easier to mix than those without nanoparticles [85] and to contain fewer air voids or internal micro-cracks [86].…”
Section: Nanoparticle Reinforcementmentioning
confidence: 99%
“…The other constituents were polymeric materials which do not present peaks in an XRD pattern but appear as wide bands due to their amorphous structure. Other studies also showed that SiO 2 is the major component of this material [36][37][38][39][40]. On the other hand, ZrO 2 presented a crystalline structure, with characteristic peaks in the XRD pattern (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…Nanodentistry is an emerging area in dentistry and uses nanostructured materials to diagnose, treat and prevent oral diseases, and exhibit improved properties compared to conventional ones 31 . In particular, there is much expectation regarding the use of AgVO 3 .…”
Section: Resultsmentioning
confidence: 99%